Sumber Energi Listrik Menggunakan Pikohidro Generator Dengan Aliran Air Tandon - Farhan Alif; Kun Fayakun; Rosalina, Rosalina; Emilia Roza; Ramza, Harry (Universitas Mandiri, 2023)
Electrical energy plays a much needed role in people's lives and economic development. Alternative energy potential, especially water energy, is a solution to utilize it as an energy source. Pico Hydro Power Plant is a tool or medium that uses water. At this time a hydro power generation system is being developed that produces electrical energy, one of which is using a pico hydro generator where the flow rate of water can be converted into electrical energy. In the water piping system at home it is used as a source of electricity, namely where the water reservoir as a reservoir for clean water with water conditions that are affected by the water flow rate can drive a pico-hydro generator turbine. In this research, the data collection process was obtained with a process of taking every 2 minutes for 40 minutes, it obtained an average water discharge of 8.75 L/s with a cross-sectional area of ​​0.0531, so the pico hydro generator can produce an average voltage of 8.88 Volts where the output results are step Up for battery charging and the average power is 10.60 watts on the battery using 3 loads and this research can be used for home lighting.